Chemically Integrating MXene Nanosheets with N-Doped C-Coated Si Nanoparticles for Enhanced Li Storage Performance. (1st July 2021) - Jo, Du Yeol; Kim, Jin Koo; Oh, Hong Geun; Kang, Yun Chan; Park, Seung-Keun
Abstract: Herein, ternary composite composed of Si@N-doped C coupled with 2D MXene nanosheets (Si@NC/MX) is synthesized by a facile solution-based chemical method followed by thermal treatment. In the aqueous solution, polydopamine (PDA)-coated Si nanoparticles were strongly coupled with MXene nanosheets via chemical interactions. Subsequently, the PDA layers were transformed into N-doped amorphous C during the annealing process. As anodes for Li-ion batteries (LIBs), the rational architecture of composites can effectively prevent particle aggregation and restacking between MXene nanosheets during cycling. Also, the dual protection by the C layer and MXene can alleviate the large volume expansion of the Si anode and provide conductive pathways. Accordingly, the Si@NC/MX composites exhibited a high reversible capacity of 953 mA h g −1 after 300 cycles at 1 A g −1 . In addition, the electrode exerted a high reversible capacity of 849 mA h g −1 even at a high current density of 10 A g −1 . Graphical abstract: Image, graphical abstract